The Use of Artificial Intelligence Technology in the Teaching Process in East Belitung City - Shohib Khoiri; Ziaul Haq, Sansan; Siregar, Qoriah; Silvia Nur Aulia, Elsa (ENGAGEMENT: Jurnal Pengabdian Masyarakat, 2024)
This study aims to examine the influence of artificial intelligence (AI) technology on human life. Based on the research conducted, AI has an influence on every sector of their lives, including health, transportation, work activities, and education. In general, AI has a positive impact, namely convenience and efficiency in several sectors. Because of this positive impact, the use of AI is currently very massive. For the education sector, AI has spread its use in many regions in Indonesia, one of which is East Belitung City in Banka-Belitung Province. Based on the results of the research conducted, it was concluded that teachers in East Belitung City already know and use AI in their teaching process. This research was conducted using qualitative and quantitative methodologies. Qualitative methodology is used to examine the influence and role of AI in human life in general, while quantitative methods are used to record the use of AI by teachers in East Belitung City, begins by providing materials related to AI, with training in its use.